Unaltered pneumococcal carriage prevalence due to expansion of non-vaccine types of low invasive potential 8 years after vaccine introduction in Stockholm, Sweden. Issue 38 (31st August 2016) - Lindstrand, Ann; Galanis, Ilias; Darenberg, Jessica; Morfeldt, Eva; Naucler, Pontus; Blennow, Margareta; Alfvén, Tobias; Henriques-Normark, Birgitta; Örtqvist, Åke
Highlights: 94% of pneumococcal carriage strains were of non-vaccine serotypes 8 years post-PCV. Low invasive disease potential for most emerging non-vaccine types in carriage. High invasive disease potential for non-vaccine serotypes 22F, 8, 12F and 9N. No change in antibiotic resistance among pneumococcal isolates after PCV introduction. Abstract: Objective: To evaluate the carriage prevalence, serotype distribution, and antibiotic resistance for pneumococcal carriage isolates collected 4–8 years after introduction of pneumococcal conjugate vaccines (PCVs) in Stockholm, Sweden, and to identify risk factors for carriage and calculate the invasive disease potential for emerging serotypes. Methods: Nasopharyngeal aspirates were collected from 3024 children aged 0–<5 years at regular visits at 23 Child Health Centers in Stockholm County in 2011–2015, and from 787 parents in 2014–2015. The invasive disease potential was calculated for serotypes using invasive disease isolates from 824 patients of all ages identified in the Stockholm County during the same time period as the carriage isolates. Results: A total carriage prevalence of 30% did not change during the study period. Non-vaccine types (NVT) dominated (94% by 2015) and the most common serotypes in descending order were 11A, 23B, 35F and 21. Risk factors for carriage were: age ⩾3 months–<3 years, having siblings, attending day-care and having travelled abroad the last 3 months. Antibiotic resistance remained low. The invasive disease potential was high for NVT 8, 9N, 12F, and 22F, while low for a majority of emerging NVTs in carriage. Conclusion: The carriage prevalence remained the same 4–8 years after vaccine introduction, but serotype replacement became almost complete. A majority of emerging NVTs in carriage showed a low invasive disease potential. Carriage studies are an important complement to invasive disease surveillance to understand the full effect of PCV vaccine programs.